2007
DOI: 10.1073/pnas.0610257104
|View full text |Cite
|
Sign up to set email alerts
|

Freshly excavated fossil bones are best for amplification of ancient DNA

Abstract: Despite the enormous potential of analyses of ancient DNA for phylogeographic studies of past populations, the impact these analyses, most of which are performed with fossil samples from natural history museum collections, has been limited to some extent by the inefficient recovery of ancient genetic material. Here we show that the standard storage conditions and/or treatments of fossil bones in these collections can be detrimental to DNA survival. Using a quantitative paleogenetic analysis of 247 herbivore fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(120 citation statements)
references
References 21 publications
7
109
2
2
Order By: Relevance
“…It has been demonstrated that the ancient remains are most susceptible to contamination at the excavation process 32 and subsequent museum preservation. 33 However, from our results, it seems that well preserved teeth are less sensible to these routes of contamination. In our case, the archeologist sequence was not retrieved from the external extracts, possibly due to its elimination by later anthropologists handling.…”
Section: Discussioncontrasting
confidence: 49%
“…It has been demonstrated that the ancient remains are most susceptible to contamination at the excavation process 32 and subsequent museum preservation. 33 However, from our results, it seems that well preserved teeth are less sensible to these routes of contamination. In our case, the archeologist sequence was not retrieved from the external extracts, possibly due to its elimination by later anthropologists handling.…”
Section: Discussioncontrasting
confidence: 49%
“…It is well known that treatment and storage conditions of samples can dramatically reduce and degrade endogenous DNA (Pruvost et al, 2007;Staats et al, 2011). Evidence from our shotgun sequencing data suggests that the old herbarium samples utilized here contain low levels of endogenous DNA and exhibit damage patterns typical of ancient DNA.…”
Section: Sequencing Chloroplast Genomes From Extinct and Ancient Planmentioning
confidence: 80%
“…This site was excavated 10-15 years ago, and differently from Apollo Klarios, skeletons from the Lower Agora were unearthed without the necessary precautions for avoiding contamination, this confirming how crucial the post-excavations procedures are for aDNA investigations. 40 Within the context described in the introduction, the mtDNA pool of the Byzantine population of Sagalassos brings new elements to estimate the genetic signature associated to the historic/demographic events, which took place in this region since the Bronze Age. The results of our study point to a West-Eurasian composition of the mtDNA gene pool of the 11th-13th-century Byzantine population.…”
Section: Discussionmentioning
confidence: 99%